IMPACTS OF SCHIZOPHRENIA IN THE FAMILY CONTEXT: reports of experiences with relatives who attend support groups in a CAPS of a city in the interior of the Zona da Mata, Minas Gerais - Vieira Costa, Betânia; Braga de Aquino, Giselle; Carlos Ferreira, Bruno (LINKSCIENCEPLACE, 2026)
The aim of the study was to identify how the family context works when there is a member with psychiatric disorder, such as schizophrenia; besides analyzing how the process of social isolation of people with mental disorder that has occurred for years, interfered and interferes in the relationship with the family. To carry out the study, we used bibliographic research and a qualitative research through interviews with relatives of patients diagnosed with schizophrenia, who attend support groups in a CAPS. The interviews were transcribed in their entirety and the resulting texts were submitted to a Discourse Analysis (ROCHA-COUTINHO, 1998) from the categories of analysis: the family; the family-to-person look, diagnosis, and treatment; the family relationship and the implications in the daily life; the family and social relations; and the support network.